1981
DOI: 10.1093/ajcn/34.6.1103
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lipid and lipoprotein cholesterol concentrations in adult males consuming normal and high cholesterol diets under controlled conditions

Abstract: Twenty-three young adult males were fed diets containing either 400 or 1400 mg of cholesterol per day under controlled conditions for 4 wk. There were minimal differences between the two diets in total protein, carbohydrate, fat, and the P/S fatty acid ratio. In both diets 400 mg of cholesterol was supplied from nonegg food sources; the additional 1000 mg of cholesterol was from four whole eggs. Blood samples were collected after a 12- to 14-h fast at the beginning of the study, weekly throughout the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…with controls. According to a study that investigated total TG levels from participants who were fed diets with either 1400 or 400 mg of cholesterol per day for a month, TG levels increased slightly but not as dramatically as 10-fold [26]. Similar result was observed from this study in agreement, in which levels of only 3 TG species were significantly altered (> 10-fold) by metabolic factors.…”
Section: Resultssupporting
confidence: 88%
“…with controls. According to a study that investigated total TG levels from participants who were fed diets with either 1400 or 400 mg of cholesterol per day for a month, TG levels increased slightly but not as dramatically as 10-fold [26]. Similar result was observed from this study in agreement, in which levels of only 3 TG species were significantly altered (> 10-fold) by metabolic factors.…”
Section: Resultssupporting
confidence: 88%
“…In addition, excess sterol is reexcreted in the bile so that many individuals in this way are able to compensate to some extent for the increased cholesterol load (33). Undoubtedly this contributes to the recognised variability in the response of lipoprotein cholesterol to dietary sterol supplementation (20,28,29,33). Evidence for suppressed intestinal and hepatic LDL receptor activity in response to cholesterol feedinig is much more difficult to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…The above procedure was repeated following 4 wk of high cholesterol feeding (6 eggs/d) when new steady-state LDL cholesterol levels would have been attained (28,29). The results obtained on the two occasions were compared by paired Student's t test.…”
Section: Introductionmentioning
confidence: 99%
“…Nineteen unique trials among 21 publications (8,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56) reported outcome data on dietary cholesterol and serum cholesterol concentration. Seventeen of the 19 unique trials (8,(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)56) reported quantitative data and were included in metaanalysis ( Table 2).…”
Section: Intervention Studiesmentioning
confidence: 99%